Pengolahan Limbah Tempe dan Kotoran Sapi Menjadi Biogas Dan Pupuk Organik Cair di Kampung Cilokotot Kapupaten Bandung - Murdikaningrum, Galu; Muliati, Lia; Sitawati, Rini (DHARMA BAKTI, 2024)
Cilokolot Village, RT 02 RW 02, Margahayu Selatan, Bandung Regency, is a densely populated area where traditional tempeh production occurs. In this village, there are two small-scale tempeh factories involving seven artisans, processing approximately 700 kg of soybeans daily. This study focuses on one factory, which is smaller and utilizes traditional technology, with a production capacity of 200 kg per day and firewood as its fuel source. The tempeh production process consists of boiling, soaking, separating, washing soybeans, fermenting, and packaging, which generates significant volumes of liquid waste. One of the tempeh artisans also has a livestock farm with ten cattle, fifteen goats, and a few turkeys, ducks, and chickens. Waste from tempeh and animal manure is often discharged directly into rivers and vacant land, leading to air, soil, and water pollution, which poses health risks. Biogas energy is produced through microbial processing of organic waste, such as vegetable scraps, fruit peels, leftover rice, livestock manure, and tempeh waste. The main components of biogas are methane and carbon dioxide. The objectives of this study are: 1) to educate artisans on the negative impacts of tempeh waste and livestock manure on the environment; 2) to install a Wastewater Treatment Plant (WWTP) for managing tempeh waste and cattle manure; 3) to provide training and support for processing tempeh waste and animal manure into biogas and Liquid Organic Fertilizer (LOF); and 4) to conduct training on the application of LOF to crops. The methods employed include outreach, training, technology implementation, ongoing support, and evaluation. The results indicate that: 1) artisans actively participated in socialization sessions addressing the negative impacts of tempeh waste and livestock manure; 2) the WWTP for tempeh waste and cattle manure has been successfully installed on land provided by the artisans; 3) training and support for operating the WWTP resulted in the successful production of biogas and LOF, which provide added value and benefits; and 4) training on the application of LOF to demonstration plots has been conducted, with enthusiastic participation from the artisans.